"Only a God Can Resist a God." Political Theology between Polytheism and Gnosticism. Issue 6 (18th August 2019) - Vatter, Miguel
ABSTRACT: Sovereignty – based on a claim to irresistible authority – and "speaking truth to power" (or parrhesia ) are evidently opposed and yet they seem to have a strange affinity with one another, at least if one follows Foucault's last lectures on this motif of political philosophy. This article revisits Hans Blumenberg's reconstruction of the meeting between the German poet Goethe and the French emperor Napoleon as an example of a parrhesiastic encounter between philosophy and tyranny. The article situates Blumenberg's discussion of Goethe's pantheism and polytheism in the context of his ongoing polemic with Schmitt's conceptions of sovereignty and political theology. It argues that while both Blumenberg and Schmitt seek to offer responses to the Gnostic rejection of worldly power, a reading of Goethe in light of the discourse on parrhesia or frank speech lately revived by Foucault allows for the articulation of republican response to Gnosticism.